2015
DOI: 10.1007/s00216-015-8612-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification and analytical characteristics of synthetic cannabinoids with an indazole-3-carboxamide structure bearing a N-1-methoxycarbonylalkyl group

Abstract: Illicit new psychoactive substances (NPS) are a serious threat to health throughout the world. Such NPS do not usually pass preliminary pharmacological trials. In 2014, we identified a series of five new synthetic cannabinoids with an indazole-3-carboxamide structure bearing an N-1-methoxycarbonylalkyl group. The compounds have very high cannabimimetic activity which has caused mass severe intoxication and deaths. The compounds were identified by means of gas chromatography-mass spectrometry (GC-MS), including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 25 publications
2
54
0
Order By: Relevance
“…The difference between the protonated molecule of 5 and MMB-FUBINACA (C 21 H 23 FN 3 O 3 + ) [28,29] was an additional CH 2 [28] The 13 C NMR spectrum of 5 was similar to that of MMB-FUBINACA, [28] except for the O-ethyl moiety (positions 1″' to 2″') as shown in Table 6. The difference between the protonated molecule of 5 and MMB-FUBINACA (C 21 H 23 FN 3 O 3 + ) [28,29] was an additional CH 2 [28] The 13 C NMR spectrum of 5 was similar to that of MMB-FUBINACA, [28] except for the O-ethyl moiety (positions 1″' to 2″') as shown in Table 6.…”
Section: Characterization Of 5f-akb-48-7n (3)mentioning
confidence: 87%
“…The difference between the protonated molecule of 5 and MMB-FUBINACA (C 21 H 23 FN 3 O 3 + ) [28,29] was an additional CH 2 [28] The 13 C NMR spectrum of 5 was similar to that of MMB-FUBINACA, [28] except for the O-ethyl moiety (positions 1″' to 2″') as shown in Table 6. The difference between the protonated molecule of 5 and MMB-FUBINACA (C 21 H 23 FN 3 O 3 + ) [28,29] was an additional CH 2 [28] The 13 C NMR spectrum of 5 was similar to that of MMB-FUBINACA, [28] except for the O-ethyl moiety (positions 1″' to 2″') as shown in Table 6.…”
Section: Characterization Of 5f-akb-48-7n (3)mentioning
confidence: 87%
“…Regarding the pharmacological effect of this compound, it might be referred as a synthetic cannabinoid (SCB) or cannabimimetic drug. Even though MDMB-FUBINACA is available worldwide via the Internet and the abuse of the drug seems to be increasing [1] there is little to no scientific/medical data concerning the pharmacology, pharmacokinetics, biotransformation or toxicology of the drug. Animal studies of intraperitoneal ( i.p .)…”
Section: Introductionmentioning
confidence: 99%
“…Hypothermia and bradycardia are typically observed following administration of cannabinoids like tetrahydrocannabinol (THC), as well as, with structurally distinct cannabimimetic indole and indazole derivatives, in rats [3] and mice [4, 5]. Additionally, in vitro binding studies have demonstrated that MDMB-FUBINACA is a potent agonist for the CB1 and CB2 receptors [1, 2]. MDMB-FUBINACA is presently unscheduled by US Drug Enforcement Agency (DEA).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have involved the use of both LC and GC coupled to HRMS. Schevyrin et al [22][23][24] published a series of articles reporting the detection of several SCs for the first time in smoke mixtures from Russia and Belarus using both LC and GC coupled to QTOF-MS. The combination of both chromatography methods was used in lieu of these compounds having spectra in commercial libraries for GC-MS.…”
Section: Conventional Separation Techniques Coupled To Hrmsmentioning
confidence: 99%
“…Powders and crystalline solids were largely prepared using solvent extraction or dilution typically with methanol or acetonitrile for MS analyses utilizing LC or GC separation. Schevyrin et al [22][23][24] dissolved smoke mixtures in methanol followed by an additional filtration step with a cellulose membrane. The extraction of blotter papers has been achieved by soaking the paper in methanol for 6 hours [25][26][27].…”
Section: Seized Materials and Purchased Legal Highsmentioning
confidence: 99%